CS014 is a novel HDAC inhibitor regulating the platelet activity, fibrinolysis and clot stability for prevention of thrombosis without increased risk of bleeding. (3rd October 2022) - Holinstat, M; Adili, R; Stanger, L; Hoang, T; Lambert, S; Rhoads, N; Dahlof, B; Bergh, N
Abstract: Background: Cardiovascular disease is the leading cause of morbidity and mortality. A major challenge with current antithrombotic treatments is the increased risk of bleeding associated with effective inhibition of clot formation. We have developed a novel histone deacetylase inhibitor (HDACi) that effectively prevents occlusive thrombosis following vascular injury without increasing bleeding diathesis commonly associated with antithrombotic drugs. Purpose: Develop an HDACi and antiplatelet drug, CS014, with an improved efficacy/safety profile and reduced bleeding risk compared with current anticoagulant and antiplatelet therapeutic approaches used to prevent thrombosis. Methods: We assessed thrombosis and bleeding in mouse models by labelling platelets and fibrin and measuring accumulation at the site of injury using intravital microscopy. Drug was administered IP for 5 days prior to the experiments. Degree of clot formation in the vessel was assessed in the 1) laser-induced cremaster thrombosis assay, 2) carotid artery FeCl3 thrombosis assay, and 3) saphenous vein rebleeding laser-induced puncture wound assay. Bleeding was assessed in the tail vein bleeding assay. Potential off-target effects were studied using thromboelastography (TEG). Results: CS014 treatment significantly reduced clot formation and fibrin formation at the site of injury in the laser-induced cremaster arteriole thrombosis assay (Fig. 1). FeCl3-induced injury of the carotid artery resulted in full occlusion of the carotid artery within 12–15 minutes. Treatment with CS014 was able to prevent full occlusion of the carotid artery, supporting its benefit in arterial injury conditions. In the saphenous vein rebleeding assay, fibrin and platelet accumulation at the site of injury wound was significantly inhibited, suggesting that CS014 functions in both arterial and venous systems to attenuate clot and thrombosis. The tail vein bleeding assay confirmed that while the thrombus formation and stability was decreased based on the cremaster and carotid artery assays, no significant change was observed in bleeding time under these conditions. Finally, TEG experiments in mouse blood treated with or without CS014 demonstrated no delay or decrease in clot strength confirming the prevention of a bleeding diathesis observed in the tail vein bleeding assay experiments. Conclusions: We have shown for the first time that the HDACi CS014 results in inhibition of mouse thrombosis and decreased time to clot resolution without an increased risk of bleeding. This discovery represents a new class of inhibitors for prevention of platelet activation and thrombosis with the potential to protect from myocardial infarction and stroke while increasing fibrinolytic ability in the blood to limit the risk of thromboembolism on the venous side, with no signs of increased bleeding risk. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Cereno Scientific